2009
DOI: 10.1242/jcs.041632
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α9β1 mediates enhanced cell migration through nitric oxide synthase activity regulated by Src tyrosine kinase

Abstract: Integrins are important mediators of cell adhesion and migration, which in turn are essential for diverse biological functions, including wound healing and cancer metastasis. The integrin α9β1 is expressed on numerous mammalian tissues and can mediate accelerated cell migration. As the molecular signaling mechanisms that transduce this effect are poorly defined, we investigated the pathways by which activated integrin α9β1 signals migration. We found for the first time that specific ligation of integrin α9β1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 56 publications
1
67
0
1
Order By: Relevance
“…Thus, the improved wound healing by this compound was likely a result of cells migrating into the wounded area. Other studies have also shown that NO increases cell migration, but it can also inhibit motility, depending on the type of cell, level and duration of NO exposure, and assay conditions [44][45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the improved wound healing by this compound was likely a result of cells migrating into the wounded area. Other studies have also shown that NO increases cell migration, but it can also inhibit motility, depending on the type of cell, level and duration of NO exposure, and assay conditions [44][45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, integrin signaling modifies NO production. Activation of integrin alpha9/beta1 stimulates iNOS, thereby increasing NO production [108]. Signaling through integrin and integrin-linked kinase has been shown to regulate the expression of iNOS [109].…”
Section: Discussionmentioning
confidence: 99%
“…Integrins are thought to regulate glial migration to, and contact with, target cells, thereby playing a critical role in positioning glial cells. Cooperation and crosstalk between NO and integrins have been investigated in platelets [105], neutrophils [106], and endothelial cells [108,109], but not in glial cells. Therefore, it is imperative that future studies are carried out in order to address how the interplay between NO and integrins impacts on glial cell functions and on the progression of pathological pain.…”
Section: Discussionmentioning
confidence: 99%
“…4C, right), suggesting the possible involvement of FAK-independent pathways in regulation of cadherin-11 expression beyond a9 engagement. FAKindependent PI3K signaling triggered by a9 activation (15,16) might play an important role in increasing cadherin-11 expression in FLSs under inflammatory conditions (35).…”
Section: Depletion Of A9 or Tn-c Suppresses Hyperplastic And Proinflamentioning
confidence: 99%
“…FAK is one of the first signaling molecules activated upon integrin engagement through autophosphorylation at Tyr 397 and triggers outside-in integrin signaling (14). Src and PI3K act cooperatively with FAK in this pathway but also activate FAK-independent pathways (15,16). Among various integrins expressed in FLSs, a9 is unique in that it does not bind to abundant ECM proteins such as fibronectin, laminins, vitronectin, or collagens but functions as a receptor for tenascin-C (Tn-C) (17), protease-cleaved osteopontin (18), VEGF-C (19), and thrombospondin-1 (20).…”
mentioning
confidence: 99%